Meta-analysis and systematic review of physical activity on neurodevelopment disorders, depression, and obesity among children and adolescents - Peng, Sanying; Fang, Yuan; Othman, Ahmad Tajuddin; Liang, Jinghong (Frontiers in Psychology, 2022)
Background No consensus on whether physical activity (PA) is related to physical and mental health among pediatric population remains has been reached to date. To further explore their association, our study assessed the effect of PA on physical and mental health of children and adolescents through a systematic review and meta-analysis of randomized controlled studies (RCTs). Methods Several databases(Web of science, PubMed, Embase, Cochrane Central register of controlled trials, CINAHL) were searched from inception to 1st, December 2020 without language restrictions. Results 38,236 records were identified primitively and 31 included studies with 1,255 participants eventually met our inclusion criteria, all of which exhibited a relatively low-moderate risk of bias of overall quality. In regard to mental health, the administration of PA, compared with the control group, led to moderate improvements in Autism Spectrum Disorder(ASD)[Standard mean difference (SMD) = −0.50, Confidence interval(CI): −0.87, −0.14)] and depression(SMD = −0.68, CI: −0.98, −0.38) among children and adolescents. Similarly, significant result was observed in obesity (SMD = −0.58, CI: −0.80, −0.36). No significant differences were observed in Attention deficit hyperactivity disorder (ADHD) (SMD = −0.29, CI: −0.59, 0.01). Conclusion Altogether, PA may have a beneficial effect on children and adolescents with ASD, depression and obesity; nevertheless, there is insufficient evidence to confirm its efficacy in ADHD. More large-scale population based randomized controlled trials are needed to explore more reliable evidence between them.